Association between maternal anxiety in pregnancy and increased uterine artery resistance index: cohort based study. Issue 7177 (16th January 1999) - Teixeira, Jeró;nima M A; Fisk, Nicholas M; Glover, Vivette
Abstract: Objective: To investigate whether maternal anxiety in the third trimester is associated with an increased uterine artery resistance index. Design: Cohort based study. Subjects: 100 pregnant women, with a mean gestation of 32 weeks. Outcome measures: Self rating Spielberger questionnaire for state anxiety and trait anxiety, and uterine blood flow waveform patterns as assessed by colour Doppler ultrasound. Results: A significant association was found between uterine artery resistance index and scores for both Spielberger state anxiety and trait anxiety ( r s =0.31, P<0.002 and 0.28P<0.005 respectively). Women with state anxiety scores >40 (n=15) had a higher mean uterine resistance index than those with scores —40 (mean difference with mean resistance index 24%, 95% confidence interval 12% to 38%; P<0.0001). Similarly, women with trait anxiety scores >40 (n=32) had a higher mean resistance index than those with scores —40, although to a lesser extent. The presence of notches in the waveform pattern produced by uterine artery blood flow was found in 4/15 (27%) women with high state anxiety scores compared with 4/85 (5%) with low anxiety scores (P<0.02). Conclusions: This study shows an association between maternal anxiety in pregnancy and increased uterine artery resistance index. It suggests a mechanism by which the psychological state of the mother may affect fetal development, and may explain epidemiological associations between maternal anxiety and low birth weight. The influence of maternal anxiety may be one mechanism by which the intrauterine environment contributes to later disease in offspring.